Separation of Vlc Signals Using Fastica and Infomax - Soto-Gomez, J; San Juan-Urrutia, E; Adasme-Soto, P (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper proposes two methods of separation of VLC signals, based on the stadistical variation 1) FastIca and 2) InfoMax, the first one based in the stadistical covariance of the negentrophy and the second one based in the artificial neural network for the analysis of covariance of the values from signals. This values are results of a simulation and experimental transference of information through Visible Light Communication, the simulation without noise, and the experimental process with noise. © 2017 IEEE.